ANALISIS KOMPUTASI MARGIN EXHAUST GAS TEMPERATURE PADA TIPE ENGINE IAE V2500 UNTUK MENENTUKAN RENCANA PERAWATAN - Rachmat Permadi, Rully; Widyanto, Dwi (Sekolah Tinggi Teknologi Kedirgantaraan, 2024)
Checking the exhaust gas temperature (EGT) margin of each engine is very important to know when the engine is not working properly and provide suggestions for maintenance. An engine with reduced performance becomes less efficient and requires more fuel to produce the same thrust, which causes an increase in exhaust gas temperature (EGT). This jurnal discusses EGT margin analysis on the IAE V2500 engine type and data obtained from engine 1 PK-ABC parameters from 1 October 2023 to 31 March 2024 will be calculated manually based on the Service Instruction Letter. The results of manual calculations produce the EGT Margin value for engine on March 31 2024 for engine 1 it is 61.582°C. During 6 months of research it was found that engine 1 experienced a decrease in EGT margin below the minimum (25°C) 5 times. So the results of this research recommend implementing a hot section refurbishment for engine 1